2010
DOI: 10.1007/s11307-010-0465-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cell-Proliferation-Associated Gene Expression on 2-Deoxy-2-[18F]fluoro-d-Glucose (FDG) Kinetics as Measured by Dynamic Positron Emission Tomography (dPET) in Colorectal Tumors

Abstract: The results suggest that the FDG kinetics is modulated by proliferation associated genes. Especially K1, the parameter for the FDG transport into the cells, is modulated by cdk2. Tumors with a SUV exceeding 12 have usually a higher expression of cyclin D2. The parameters of the FDG kinetics can be used to predict the expression of proliferation associated genes individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…The improved biodistribution pattern of MH 18 F over 18 FDG is due to the exclusive expression of maltohexaose transporters in bacteria in contrast to the high expression of glucose transporters in mammalian cells. [12c, 24] This allowed MH 18 F to clear from all of the major organs including heart, lung, brain, liver, bone and muscle, whereas 18 FDG had significant accumulation within these tissues. For example, in infected rats, the ratio of accumulation of MH 18 F in infected muscle versus liver was 5, whereas for 18 FDG, this ratio was only 0.3, and for other reported PET contrast agents the infected muscle to liver ratio is also generally less than 1.…”
mentioning
confidence: 99%
“…The improved biodistribution pattern of MH 18 F over 18 FDG is due to the exclusive expression of maltohexaose transporters in bacteria in contrast to the high expression of glucose transporters in mammalian cells. [12c, 24] This allowed MH 18 F to clear from all of the major organs including heart, lung, brain, liver, bone and muscle, whereas 18 FDG had significant accumulation within these tissues. For example, in infected rats, the ratio of accumulation of MH 18 F in infected muscle versus liver was 5, whereas for 18 FDG, this ratio was only 0.3, and for other reported PET contrast agents the infected muscle to liver ratio is also generally less than 1.…”
mentioning
confidence: 99%
“…Actually it can be expected that inhibitors of the cell cycle usually reveal a negative correlation to PET parameters. Based on our results in colorectal carcinoma, we were able to show that cdki 2B was negatively correlated with k3 [5]. In contrast, cdk2 was positively correlated with the SUV in these tumors.…”
Section: Discussionmentioning
confidence: 94%
“…The tracer kinetics of FDG is closely dependent on the expression of glucose transporters and hexokinases. However, it was shown that the kinetics of FDG may be modulated by genes associated with angiogenesis and proliferation [4, 5]. Thus, gene expression may be predicted from a detailed analysis of the FDG kinetics in certain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the kinetic model in particular k 1 was correlated with the expression of the angiogenesis-related genes. In the same topic and more recently Strauss et al [54] showed in their study on 25 patients that FDG kinetics model in particular the parameters for the transport ( k 1 ) was related with the genes of proliferation, which means that the biological behaviour including angiogenesis and cellular proliferation may be predicted in the light of kinetic data.…”
Section: Kinetic Analysis Of Pet Imaging In Colorectal Tumoursmentioning
confidence: 97%